1983
DOI: 10.1148/radiology.149.2.6622678
|View full text |Cite
|
Sign up to set email alerts
|

Effects of contrast media on pulmonary hemodynamics: comparison of ionic and non-ionic agents.

Abstract: Hemodynamic effects of pulmonary arterial injections of ionic (sodium methylglucamine diatrizoate) and non-ionic contrast media (iohexol) were compared in 9 anesthetized dogs which were maintained with an open thorax in a resting control state. Both were found to increase pulmonary arterial pressure and cardiac output. In addition, both resulted in decreased systemic vascular resistance, though the effect was significantly less with the non-ionic agent. Aortic pressure did not change with the non-ionic agent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…As such, the difference in perfusion values between normal subjects and those with PPH may have been overestimated. Secondly, radiographical contrast agents, even nonionic media, are known to have mild vasodilatory properties [23,24]. The relative importance of this effect in the increase in perfusion seen with the addition of adenosine in patients with PPH is difficult to quantify, but in previous work, where subjects have been studied under the same conditions on two occasions, the effects seem to be minimal [4].…”
Section: Discussionmentioning
confidence: 99%
“…As such, the difference in perfusion values between normal subjects and those with PPH may have been overestimated. Secondly, radiographical contrast agents, even nonionic media, are known to have mild vasodilatory properties [23,24]. The relative importance of this effect in the increase in perfusion seen with the addition of adenosine in patients with PPH is difficult to quantify, but in previous work, where subjects have been studied under the same conditions on two occasions, the effects seem to be minimal [4].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the indicator must mix completely with blood, should be as near as possible a bolus and must not itself influence flow. Others have shown that radiographic contrast material may influence regional pulmonary blood flow [20,21], although comparison of the results from repeated measurements in the current study made before and after each intervention (hypoxia, hypoxia plus NO) would effectively control for such variability.…”
Section: Discussionmentioning
confidence: 87%
“…An increase in pulmonary artery pressure has been reported following the intravascular injection of contrast media (Frisinger et al 1965;Almen et al 1980;Mills et al 1980;Peck et al 1983;Schrader et al 1987;Nicod et al 1987;Rees et al 1988;Tajima et al 1994;Pitton et al 1996;Sunnegardh et al 1990;Sorenson et al 1994). This sudden increase in pulmonary artery pressure is thought to contribute to the morbidity and mortality associated with pulmonary angiography, particularly in patients with pulmonary hypertension (Schrader et al 1987;Nicod et al 1987;Rees et al 1988;Tajima et al 1994;Pitton et al 1996).…”
Section: Effects Of Contrast Media On Pulmonary Circulationmentioning
confidence: 98%
“…This sudden increase in pulmonary artery pressure is thought to contribute to the morbidity and mortality associated with pulmonary angiography, particularly in patients with pulmonary hypertension (Schrader et al 1987;Nicod et al 1987;Rees et al 1988;Tajima et al 1994;Pitton et al 1996). There are conflicting reports in the literature about the mechanisms responsible for these effects (Almen et al 1980;Peck et al 1983;Schrader et al 1984Schrader et al , 1987Rees et al 1988;Sunnegardh et al 1990;Sorenson et al 1994;Kuhtz-Buschbeck et al 1997;Emery et al 2001). Some studies showed that the rise in pulmonary artery pressure is secondary to an increase in pulmonary vascular resistance (PVR) (Schrader et al 1984;Emery et al 2001), whereas others indicated that it is due to an increase in cardiac output associated with a decrease in pulmonary vascular resistance (Almen et al 1980;Sunnegardh et al 1990;Sorenson et al 1994;Kuhtz-Buschbeck et al 1997).…”
Section: Effects Of Contrast Media On Pulmonary Circulationmentioning
confidence: 99%
See 1 more Smart Citation